2018
DOI: 10.3389/fped.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sex on Gestational Complications, Fetal-to-Neonatal Transition, and Postnatal Adaptation

Abstract: Fetal sex is associated with striking differences during in utero development, fetal-to-neonatal transition, and postnatal morbidity and mortality. Male sex fetuses are apparently protected while in utero resulting in a higher secondary sex rate for males than for females. However, during fetal-to-neonatal transition and thereafter in the newborn period, female exhibits a greater degree of maturation that translates into a better capacity to stabilize, less incidence of prematurity and prematurity-associated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…In males, lung maturation is delayed compared to females, and male newborn infants have higher incidences of birth asphyxia as well as common neonatal disorders linked to oxidative stress. It has been suggested that the lower antioxidant capacity in males results in increased risk of pulmonary vasoconstriction, vascular instability, and hypoxia [ 25 ]. These constitutional differences between boys and girls might explain some of the preponderance of SDH in boys.…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
“…In males, lung maturation is delayed compared to females, and male newborn infants have higher incidences of birth asphyxia as well as common neonatal disorders linked to oxidative stress. It has been suggested that the lower antioxidant capacity in males results in increased risk of pulmonary vasoconstriction, vascular instability, and hypoxia [ 25 ]. These constitutional differences between boys and girls might explain some of the preponderance of SDH in boys.…”
Section: Discussion Principal Findingsmentioning
confidence: 99%
“…Boys are at greater risk than girls for perinatal adversities. Male infants undergo Caesarean section (OR 1.2) have low Apgar scores (OR 1.5) and experience severe hypoxic ischaemic encephalopathy (OR 1.2) more often than female babies . Reviews of the literature have also found that male infants react more frequently than females to a variety of adversities and hardships including infections, preterm birth, respiratory problems and toxic exposures during perinatal life .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, male feto-placental units adopt a more "minimalist approach" where they undergo very few placental changes and continue to grow normally under adverse in utero environment. However, this adaptation places male fetuses at higher risk to exposures that may contribute to deleterious health impacts on later development due to environmental toxins and/or sub-optimal maternal nutrition [9][10][11] .…”
mentioning
confidence: 99%